2023
DOI: 10.3390/rs15215172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atmospheric Carbon Dioxide Concentrations Based on GOSAT, OCO-2 Observations and Ground-Based TCCON Data

Jinhui Zheng,
Huifang Zhang,
Shuai Zhang

Abstract: Carbon dioxide (CO2) is one of the most significant greenhouse gases, and its concentration and distribution in the atmosphere have always been a research hotspot. To study the temporal and spatial characteristics of atmospheric CO2 globally, it is crucial to evaluate the consistency of observation data from different carbon observation satellites. This study utilizes data from the Total Carbon Column Observing Network (TCCON) to verify the column-averaged dry air mole fractions of atmospheric CO2 (XCO2) retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…This adjustment can effectively increase the consistency of the data and help eliminate the noise and error caused by the small fluctuations of the data. Zheng et al 37 found that the standard error of XCO 2 between TCCON and GOSAT lite products was found to be 1.20 ppm, and the standard error between TCCON and OCO-2 OCO2_L2_Lite_FP_10r was 0.97 ppm. Because the OCO-3 satellite was recently launched and there is no corresponding validation study for the OCO3_L2_Lite_FP_10.4r data, we assume that its standard error is also 0.97 ppm.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…This adjustment can effectively increase the consistency of the data and help eliminate the noise and error caused by the small fluctuations of the data. Zheng et al 37 found that the standard error of XCO 2 between TCCON and GOSAT lite products was found to be 1.20 ppm, and the standard error between TCCON and OCO-2 OCO2_L2_Lite_FP_10r was 0.97 ppm. Because the OCO-3 satellite was recently launched and there is no corresponding validation study for the OCO3_L2_Lite_FP_10.4r data, we assume that its standard error is also 0.97 ppm.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…They indicated that Tansat XCO 2 had the highest accuracy with an R 2 of 0.88 and an RMSE of 1.06 ppm, followed by OCO-2 XCO 2 with an R 2 of 0.82 and an RMSE of 1.07 ppm, and ACOS-GOSAT XCO 2 had the lowest accuracy with an R 2 of 0.81 and an RMSE of 1.23 ppm. Zheng et al [25] validated the OCO-2 XCO 2 product from September 2014 to February 2022 and the ACOS-GOSAT XCO 2 product from April 2009 to May 2016 using 20 TCCON stations and found that OCO-2 and ACOS-GOSAT XCO 2 products showed strong correlation with TCCON XCO 2 with R 2 of 0.91 and 0.85, respectively. Karbasi et al [26] validated the GOSAT XCO 2 product retrieved by ACOS, NIES, and SRFP algorithms from 2009 to 2021 using 8 TCCON stations.…”
Section: Introductionmentioning
confidence: 99%